Pemetaan Atraksi Wisata Sepanjang Jalur Penghubung (Transit Route) Badung-Bedugul - Roslandari, Luh Putu Ratih; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p01, 2018)
The development of the tourism industry currently leads to the main lines that becomes a link between tourists generating regions and tourists destination regions. This study aims to assess the current development of a tourist attraction in the transit route that can be monitored through the mapping process and the division of the tourism clusters based on tourism products and location . The location of this research is located in the transit route along between of Badung - Regency and Bedugul . The data sources are from primary and secondary data. Methods of collecting the datas are interview and observation. In this report, the data presented in the form of a map based on observations and interviews. This research’s scope is limited by the concept of tourist attractions, concept of tourism clusters and concept of transit regions. The results - obtained from this research is there are mapping of tourist attractions based on administration territory along the transit route. Tourist attractions are divided into two types, natural tourist attractions and artificial tourist attractions. Tourist attractions in the transit route are concentrated based on tourism products and location tourist attraction . The tourist attractions are located in the middle of five villages that adjacently with Badung - regency as tourist generating regions and Bedugul as tourist destination regions.   Keywords : Mapping, Tourist Attraction Featured, Transit Route